THE ROLE OF THE SPECIAL AUTONOMY FUND TO IMPROVE THE PUBLIC SERVICE IN THE PAPUA PROVINCE - Ginting, Ari Mulianta (Jurnal Ekonomi & Kebijakan Publik, 2023)
This paper examines the special autonomy fund's role in public service in health and education sector in districts/cities in Papua Province. Using panel data from 29 districts/cities in Papua Province covering 2013-2020, our findings are based on panel data. The special autonomy fund has a positive and significant impact on public service in health and education sector in districts/cities in Papua Provinces. Moreover, we identify that fiscal decentralization also positively and significantly affects public service in districts/ cities in Papua Province. A special autonomy fund is a necessary condition for increasing public service. There are requirements to implement the special funding for Papua, such as participation of the people in determining and supervising the use of the special fund, accountability of local government to use the special fund, synergy, and coordination among stakeholders in Papua. Finally, the central government must ensure that special funds must be allocated to public services such as health and education sector. Indonesian Parliament should make an evaluation and monitoring of the special autonomy fund for Papua Province. The evaluation and monitoring of the special autonomy fund are needed in order to fulfill the aims of the fund. Keywords: fiscal policy, public economics, regional autonomy, special autonomy fund, public serviceAbstrakTulisan ini mengkaji peran dana otonomi khusus (otsus) terhadap pelayanan publik baik di bidang kesehatan maupun pendidikan di kabupaten/kota di Provinsi Papua. Menggunakan data panel dari 29 kabupaten/kota di Provinsi Papua tahun 2013-2020, temuan kami didasarkan pada data panel. Dana otsus berdampak positif dan signifikan terhadap pelayanan publik baik di bidang kesehatan maupun pendidikan di kabupaten/kota di Provinsi Papua. Selain itu, kami mengidentifikasi desentralisasi fiskal juga berpengaruh positif dan signifikan terhadap pelayanan publik di kabupaten/kota di Provinsi Papua. Dana otsus merupakan prasyarat untuk peningkatan pelayanan publik. Ada persyaratan untuk melaksanakan dana khusus untuk Papua, seperti partisipasi masyarakat dalam menentukan dan mengawasi penggunaan dana khusus, akuntabilitas pemerintah daerah untuk menggunakan dana khusus, sinergi, dan koordinasi para pemangku kepentingan di Papua. Terakhir, pemerintah pusat harus memastikan dana khusus harus dialokasikan untuk pelayanan publik seperti sektor kesehatan dan pendidikan. DPR RI perlu mendorong pengawasan dan evaluasi terhadap dana otonomi khusus di Provinsi Papua agar sesuai dengan tujuan pemberian dana tersebut.Kata kunci: kebijakan fiskal, ekonomi regional, ekonomi publik, ekonomi regional, Dana Otonomi Khusus Papua